The Habituation of Reading and Memorizing Short Surahs of The Qur’an in Developing Spiritual Intelligence in Students of MIS Al-Islam Bengkulu City - Eka Wulandari; Aziza Aryati; Kurniawan Kurniawan (Journal of Primary Education (JPE), 2026)
This research is motivated by the urgency of internalizing spiritual intelligence in the midst of moral challenges in the elementary school era. This study aims to analyze the implementation, implications, and supporting or inhibiting factors of the habit of reading and memorizing short surahs of the Al-Qur'an at MIS Al-Islam, Bengkulu City. Using a qualitative descriptive approach, data were gathered through in-depth interviews, participant observation, and documentation. The findings reveal that: 1) The habituation is integrated into the school’s routine program, specifically through collective morning recitations that involve all school members; 2) This practice significantly enhances students' spiritual intelligence, manifested in increased self-awareness, responsibility, and the ability to find spiritual meaning in daily activities; 3) While adequate facilities and teacher commitment act as primary catalysts, low student enthusiasm and inconsistent discipline remain key challenges. This study concludes that structured Qur'anic habituation is a vital instrument in shaping the spiritual character of students in Madrasah environments.